The dual roles of exosomes in prostate cancer: mechanisms in tumorigenesis and avenues for clinical translation - Yu, Mingyun; Zhou, Dan; Wei, Huijie; Wu, Tong; Fan, Jiahong; Ran, Guanghe; Zhang, Chong (Frontiers in Immunology, 2026)
Prostate cancer (PCa) management remains challenged by tumor heterogeneity, unpredictable progression, and limitations in early detection, driving demand for innovative biological insights. As pivotal mediators of intercellular communication, exosomes exhibit dualistic roles in PCa pathogenesis and therapy. While acting as ‘foes’ by facilitating epithelial-mesenchymal transition (EMT), angiogenesis, tumor microenvironment formation, metastasis, immune evasion, and therapy resistance, they concurrently serve as ‘friends’ through their diagnostic and therapeutic potential. Exosome-derived biomarkers enable non-invasive liquid biopsy for early diagnosis, risk stratification, and treatment monitoring. Moreover, engineered exosomes function as targeted drug carriers, delivering precision therapeutics to overcome treatment barriers. This review systematically examines exosomal biogenesis, isolation methodologies, and their bidirectional regulation in PCa progression, while exploring emerging diagnostic and therapeutic applications to advance exosome-mediated precision oncology.